Infrastructure and girls' education: Bicycles, roads, and the gender education gap in India - Moritz Seebacher (ifo Institute - Leibniz Institute for Economic Research at the University of Munich, 2022)
How can infrastructure help to reduce the gender education gap in developing countries? In this paper, I analyze the complementarity of all-weather roads and a bicycle program in Bihar, India, which aimed to increase girls' secondary school enrollment rate. Using Indian household survey data combined with a quadrupledifference estimation strategy, I find that the program's main beneficiaries are girls living at least 3km away from secondary schools whose villages are connected with all-weather roads. Their net secondary school enrollment rate increased by over 87 percent, reducing the respective gender education gap by around 45 percent. I find no effect for girls living in villages without an all-weather road, suggesting that allweather roads are not just complementary to the bicycle program but a precondition for its success. The findings highlight the importance of well-functioning infrastructure for the accessibility of secondary schools and the empowering of girls in India.
Keywords: O18; I21; I28; H42; J16; 330; Roads; bicycles; infrastructure; girls' education; gender education gap; India